Efektivitas Penggunaan Jenis Pelarut dan Asam dalam Proses Ekstraksi Pigmen Antosianin Kelopak Bunga Rosella (Hibiscus sabdariffa L) - Ryan Moulana; Juanda Juanda; Syarifah Rohaya; Ria Rosika (Jurnal Teknologi dan Industri Pertanian Indonesia, 2012)
Anthocyanin is pigments are red, purple and blue that commonly found in plants and can be used as a natural dye. One kind of plant that can be extracted as a source of natural dyes and contain anthocyanin is rosella petals flower. The use of solvents and acids are the factors that determine the quality and quantity of anthocyanin that extracted from rosella petals flower. Therefore in this study will be assessed the influence of the use of appropriate solvents and acids in the process of extraction of anthocyanin from rosella petals flower. Types used are varieties rosella sabdariffa. This research was conducted using Randomized Block Design Factorial consisting of 2 factors that is the type of solvent (J) consisting of ethanol and methanol, as well as the second factor which is the type of acid (P) consisting of tartaric acid, citric acid, and acid acetate. Based on the analysis it was found that the anthocyanin pigment (in red) in rosella petals flower is more stable in the acidic conditions (low pH). Type of acid (P) gives a very significant influence (P ≤ 0.01) toward pH values and significant influence (P ≤ 0.05) toward the intensity of the color. Type of solvent (J) that used gives a very significant influence (P ≤ 0.01) toward the intensity of the color, as well as a significant influence (P ≤ 0.05) on yield and levels of anthocyanin